Cultural and Genetic Contexts for Early Turkey Domestication in the Northern Southwest. Issue 1 (January 2016) - Lipe, William D.; Bocinsky, R. Kyle; Chisholm, Brian S.; Lyle, Robin; Dove, David M.; Matson, R.G.; Jarvis, Elizabeth; Judd, Kathleen; Kemp, Brian M.
Abstract: The turkey ( Meleagris gallopavo ) was independently domesticated in Mesoamerica and the Southwest, the latter as the only case of Native American animal domestication north of Mexico. In the upland (non-desert) portion of the American Southwest, distinctive closely related mtDNA lineages belonging to haplogroup H1 (thought to indicate domestication) occur from ca. 1 A.D. (Basketmaker II period) through early historic times. At many sites, low frequencies of lineages belonging to haplogroup H2 also occur, apparently derived from the local Merriam's subspecies. We report genetic, stable isotope, and coprolite data from turkey remains recovered at three early sites in SE Utah and SW Colorado dating to the Basketmaker II, III, and early Pueblo II periods. Evidence from these and other early sites indicates that both the H1 and H2 turkeys had a predominantly maize-based diet similar to that of humans; prior to late Pueblo II times, the birds were kept primarily to provide feathers for blankets and ritual uses; and ritualized burials indicate turkeys' symbolic value. We argue that viewing individuals from the H1 and H2 haplogroups as "domestic" versus "wild" is an oversimplification.